(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate the IgA, IgG and IgM levels in the serum samples of type 2 diabetic and Periodontal patients of the Peshawar area having different life style set up. Study Design: Case control study Place and duration of Study: This study was carried out on subjects who fulfilled our criteria and agreed to participate in the study were included. They were residents of Peshawar area and visited OPDs of Khyber College of dentistry, Peshawar during July, 2012 to June, 2013. Patients and Methods: Among 120 participants, 30 were healthy, 30 were with periodontitis, 30 had diabetes and the remaining 30 had both diabetes and periodontitis. All of them had at least 20 natural teeth. Diabetic patients had the disease history minimum of five years while the periodontal patients had clinically confirmed the disease. Blood samples were collected from each of the participant and immunoglobulins A, G and M were measured. The observed data were analyzed accordingly through standard statistical methods. Results: Male patients were found more as compared to females (ratio 1: 0.87) in the two diseases. The age range was 35 to 54 years with the mean 44+5. As per HBA1C results; 40 % had good control of diabetes, 26 % moderate while in 34 % control was poor. Immunoglobulin A and G levels were found significantly higher (p < 0.05) in the three disease groups as compared to control group. Whereas the concentration of IgM was not changed by the said diseases. Besides, the gender has no influence on the levels of the three immunoglobulins. The IgG levels increased with the increase in severity of the Periodontitis disease. While IgA showed slight decrease with the increase in clinical grades of the Diabetes disease. Conclusion: The result of the current study indicates the role of humoral immune response in the two mentioned diseases. The higher levels of immunoglobins particularly IgA and IgG might be due to protective mechanism against the weak immune response and the increased bacterial challenge in diabetes and periodontitis.